Enhancing Virtual Assistance for Mental Health Support - Ankit Baghel; Akansha Pawar; Janvi Hatwar; Devansh Shrivastav; Dr. Shruti Thakur, (International Journal of Preventive Medicine and Health (IJPMH), 2025)
This research introduces Enhancing Mental Health Support through Virtual Assistance by an efficient and Comprehensive Approach. Virtual assistant features empathetic conversation capabilities, regular symptom tracking, suggestions, and connections with psychiatrists. The project’s objectives include assessing the efficacy of virtual assistance in improving user engagement and mental health outcomes and exploring user perceptions of privacy and effectiveness. We investigate the efficacy of virtual assistants in crisis intervention, ongoing therapy support, and providing coping strategies, emphasising their role in accessibility and anonymity. Furthermore, the research explores ethical considerations, including data privacy, the importance of human oversight, and the potential for virtual assistants to complement traditional therapeutic practices. The increasing demand for mental health support has led to the exploration of innovative solutions, with virtual assistance emerging as a promising avenue. This paper examines the enhancement of virtual assistants in providing mental health support by integrating advanced technologies such as natural language processing (NLP) and machine learning (ML). These systems can offer personalized responses and resources tailored to individual needs by analysing user interactions and emotional cues.